Dillemas of Social Responsibility Accounting - Mazurowska , Marta (Studia Oeconomica Posnaniensia, 2014)
A natural implication in the growing importance of sustainable development and corporate social responsibility is the need to develop a system of accounting solutions which could provide information on the methods and results regarding the implementation of the above concepts in economic entities. The purpose of this article is to present the role of accounting in the implementation of the concept of sustainable development, and in particular for its most popular tool which is integrated reporting. The text elaborates on the genesis of the concept of sustainable development and CSR. Then attention is focused on the role of accounting in the implementation of the above-mentioned ideas as well as highlighting related dilemmas.